Oscillatory behavior of higher order nonlinear diﬀerence equations - Grace, Said R.; Graef, John R. (Mathematical Modelling and Analysis, 2020)
The authors present some new oscillation criteria for higher order nonlinear diﬀerence equations with nonnegative real coeﬃcients of the form Both of the cases n even and n odd are considered. They give examples to illustrate their results.